Flypaper Effect Analysis on Regional Expenditure in East Java Province, Indonesia - Fikri, Fauzan (Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to analyze the possibility of a flypaper effect on district and city regional spending in East Java Province, Indonesia. In this study the General Allocation Fund (DAU), Revenue Sharing Fund (DBH), and Local Own Revenue (PAD) are used as independent variables, and Regional Expenditures as the dependent variable used through panel data regression analysis. The results showed that in general from 38 districts and cities in East Java Province in 2011-2018 there was a proven flypaper effect. While DAU, DBH, and PAD have proven to have significant and positive effects on Regional Expenditures.